Analysis of enzyme reaction kinetics - Malcata, F. Xavier (Hoboken, N.J. : Wiley, 2023)
'Analysis of Enzyme Reaction Kinetics is the second set in a unique 11-volume collection on Enzyme Reactor Engineering. This two-volume set comprehensively describes rate expressions pertaining to enzymatic reactions, including modulation by physicochemical factors - as tools for prediction and control of how fast substrate(s) are transformed to products, an essential element of mass balances to, and practical operation of (enzyme) reactors. Therefore, rate expressions are mathematically derived from mechanistic postulates, and complemented by appropriate statistical approaches, in attempts to fit them to experimental data (first volume); physical and chemical modulation of reaction rate is discussed next, upon both enzyme-catalyzed and enzyme deactivation reactions (second volume)'--
Includes bibliographical references and index.
Keywords: Enzyme kinetics